2019
DOI: 10.3389/fneur.2019.00797
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Blast Wave Exposure During Multiday 0.50 Caliber Rifle Course

Abstract: Research on blast overpressure (BOP) experienced by military personnel in operations like breaching, identifies transient, measurable effects on operator readiness. Specifically, blast seems to be associated with suppressed response speed and cognitive function. This work evaluates 50 caliber weapon systems to ascertain BOP effects from the weapon usage. Marksmen were a collection of professionals who use 0.50 caliber weapon systems as part of their daily activities, and the environment measured was during a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…SRT is similar among concussed vs. non-concussed athletes ( 35 ), and the participants in this study were exposed to subconcussive overpressure conditions. The decrease in PRT and GNG subtasks is indicative of a slightly faster response that has been previously reported to occur among nearly 67% of study participants ( 29 ) and may be reflective of a “practice effect” among persons without a clinically defined concussion ( 36 ). Essentially, the participants are likely paying more attention to the task itself, which is common.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…SRT is similar among concussed vs. non-concussed athletes ( 35 ), and the participants in this study were exposed to subconcussive overpressure conditions. The decrease in PRT and GNG subtasks is indicative of a slightly faster response that has been previously reported to occur among nearly 67% of study participants ( 29 ) and may be reflective of a “practice effect” among persons without a clinically defined concussion ( 36 ). Essentially, the participants are likely paying more attention to the task itself, which is common.…”
Section: Discussionmentioning
confidence: 54%
“…OP measurements were conducted as previously described (29). All participants were exposed to 3-days of OP events, firing 4-50 rounds per day from a variety of positions (prone, seated, kneeling, standing, and supported standing from barricade).…”
Section: Overpressure Measurementsmentioning
confidence: 99%
“…The characteristics of the overpressure dosage (the most critical set include peak overpressure, impulse, and inter-exposure interval, Δt) can be easily obtained from the blast gauges worn by trainees. One successful attempt to extract these vital data is presented in the paper by our group working in collaboration with the Walter Reed Army Institute of Research (WRAIR) team lead by Dr. Kamimori (23). The significance of the availability of this kind of data is paramount: for the first time, it creates an opportunity to develop animal models based on quantified human data.…”
Section: Introductionmentioning
confidence: 99%
“…past [1,21,25,27], while reference reflected pressure was measured by 3 PCB sensors (marked as 29, 30 and 31 in Fig 1B). The representative pressure profiles captured in the incident and reflected pressure configurations by sensors from both manufacturers are presented in Fig 1C-1F.…”
Section: Plos Onementioning
confidence: 99%
“…Military personnel are often exposed to blast overpressure during training with explosives as well as heavy (e.g., mortars, rockets & machine guns) and light (rifles & pistols) weapons and during combat [1,2]. Recent research has demonstrated that exposure to blast overpressure can result in deficits in neurocognitive performance [3,4] and changes in blood biomarkers [5][6][7][8][9] in the absence of a medically diagnosable injury such as concussion.…”
Section: Introductionmentioning
confidence: 99%